2013
DOI: 10.1016/j.marpolbul.2013.05.029
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution and concentrations of petroleum hydrocarbons associated with the BP/Deepwater Horizon Oil Spill, Gulf of Mexico

Abstract: We examined the geographic extent of petroleum hydrocarbon contamination in sediment, seawater, biota, and seafood during/after the BP/Deepwater Horizon Oil Spill (April 20-July 15, 2010; 28.736667°N, -88.386944°W). TPH, PAHs, and 12 compound classes were examined, particularly C1-benzo(a)anthracenes/chrysenes, C-2-/C-4-phenanthrenes/anthracenes, and C3-naphthalenes. Sediment TPH, PAHs, and all classes peaked near Pensacola, Florida, and Galveston, Texas. Seawater TPH peaked off Pensacola; all of the above cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
118
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(140 citation statements)
references
References 27 publications
14
118
3
Order By: Relevance
“…The location in the Gulf of Mexico that we sampled most intensely, Blue Hammock Bayou, Louisiana, was impacted by crude oil and the plankton community was adversely affected by the Deepwater Horizon oil spill (Sammarco et al., 2013) (see section 1). Perhaps the presence of natural oil seeps in the Gulf of Mexico and episodic injections of crude oil into the sediment and water (Anderson, Scalan, Parker, & Behrens, 1983; Stout & Payne, 2016; Stout, Payne, Ricker, Baker, & Lewis, 2016) had imposed temporally varying selection on the copepod population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location in the Gulf of Mexico that we sampled most intensely, Blue Hammock Bayou, Louisiana, was impacted by crude oil and the plankton community was adversely affected by the Deepwater Horizon oil spill (Sammarco et al., 2013) (see section 1). Perhaps the presence of natural oil seeps in the Gulf of Mexico and episodic injections of crude oil into the sediment and water (Anderson, Scalan, Parker, & Behrens, 1983; Stout & Payne, 2016; Stout, Payne, Ricker, Baker, & Lewis, 2016) had imposed temporally varying selection on the copepod population.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of E. affinis appeared to be largely absent from the Mississippi delta region of the Gulf of Mexico following the Deepwater Horizon oil spill, but returned to this area more than a year later (see section 2 for details). An extensive survey performed in 2010 found that the E. affinis habitats we sampled in the Gulf of Mexico had been exposed to high concentrations of total petroleum hydrocarbons (TPHs) and PAHs, in seawater, seafood, and sediment (Sammarco et al., 2013) (https://web.archive.org/web/20101126225809/http://leanweb.org:80/news/latest/testing-results-returning-with-high-levels.html). A rebound of E. affinis populations through dispersal is unlikely, given their limited long‐distance swimming capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The heaviest oiling of Santa Rosa Island occurred on June 23, with all 60 km of the barrier island's southern shoreline impacted with visible free product and particulate oil. Near shore water and sediment samples from the area were reported to have elevated levels of TPH and PAHs [9]. Passive water sampling devices deployed by Allan et al [10] at the entrance to Pensacola Bay showed elevated levels of bioavailable petrogenic PAHs in August and September 2010, but only background concentrations in May, June, and July 2010, and in spring 2011 follow up sampling.…”
Section: Introductionmentioning
confidence: 98%
“…It is known that few millions of tonnes of crude oil enter maritime environment each year due to events such as natural seepages, tanker accidents and production water discharge at oil rigs. Contamination spreads to sediment and marine biota, and may drift into inland waters as oil spills reach subtidal zones, intertidal areas and further into estuaries (Lee and Page 1997;Sammarco et al 2013;Fry and Anderson 2014). Rivers and connected lakes remain vulnerable when crude oil mining or transportation takes place in river basins (Kochhann et al 2015), while any other freshwater systems may be at risk because of accidental leakage or spills owing to human error.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the damage on survivors and those that undergo contamination away from the slick may not be apparent. Although investigations that followed oil spills over years are seen in the field setting (Thomas et al 1999;Irvine et al 2006;Roberts et al 2006;Sammarco et al 2013), laboratory verification of long-term responses continues to be necessary for proper prediction of the aftermath. Controlled experiments remain important in this regard, as it allows results to be attributed to the exposure unambiguously excluding confounding effects of field heterogeneity.…”
Section: Introductionmentioning
confidence: 99%